SISTEM PENGELOLAAN LIMBAH MEDIS PADAT DI RUMAH SAKIT UMUM DAERAH (RSUD) DR. RM. PRATOMO BAGANSIAPIAPI KABUPATEN ROKAN HILIR - Rika Mianna; Jufenti Ade Fitri (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2019)
ABSTRACT Hospital is a health care institution with a preventive service activities, curative, rehabilitative and promotif. Hospital waste is waste that is generated by the activities of the hospital and other supporting activities that produce medical and non medical waste either solid or liquid that can cause disease and environmental pollution that needs special attention. This research aims to look the system of managing medical waste solid in the Regional Hospital Dr. RM. Pratomo Bagansiapiapi Rokan Hilir.This research is qualitative deskripitif with the design of the survey. The research was conducted in March-April of 2014 in the Regional General Hospital Dr. RM. Pratomo Bagansiapiapi Rokan Hilir. Informants in this study is the head of the sanitary installation 1 installation of sanitation, a member of 1 person, 2 person, janitor operator 1 person. Data obtained by using a checklist, and in-depth interviews to the executor. The results of this research show that the medical waste management system is solid ranging from sorting, collection, hauling, disposal, destruction of shelter and the end is yet to comply with the regulations. Human resources is still lacking, the funds are not a problem, the absence of Standard Operating Procedure, and the obstacles that still exist from the parsing process up to the final disposal of medical solid waste management implementation. It is recommended to the hospital to be able to create Standard Operating Procedure in the management of medical waste solid in order to trigger on the standard's rules set for the creation of a hospital environment is healthy and safe. Keywords : Medical Solid Waste, Medical Waste Management, General Hospital Dr. RM. Pratomo.